Acute Cryptogenic Stroke During West Nile Virus Infection: Case Report. (January 2021) - Peters, Steven; Brown, Kristen
West Nile virus is an emerging infection in North America but has not traditionally been associated with acute vascular events. We report a 57-year-old healthy male who developed pharyngitis and a corporeal rash, followed 1 week later by an acute cryptogenic stroke. Following successful endovascular thrombectomy, cerebrospinal fluid analysis revealed acute West Nile virus infection. While severe cases of vasculopathy have been described with flavivirus infection, stroke associated with relatively mild symptoms has not been. Given increasing evidence that viral and bacterial infections of many varieties may be stroke triggers, West Nile virus and other flaviviruses may represent an uncommon but underappreciated trigger of cryptogenic stroke. We review indirect evidence that viral endothelial tropism or a nonspecific peri-infectious inflammatory state may be causative mechanisms.